Crystal structure of Trichinella spiralis calreticulin and the structural basis of its complement evasion mechanism involving C1q - Jia, Zhihui; Yu, Wen; Li, Jingmo; Zhang, Mingming; Zhan, Bin; Yan, Liming; Ming, Zhenhua; Cheng, Yuli; Tian, Xiaolin; Shao, Shuai; Huang, Jingjing; Zhu, Xinping (Frontiers in Immunology, 2024)
Helminths produce calreticulin(CRT) to immunomodulate the host immune system as a survival strategy. However, the structure of helminth-derived CRT and the structural basis of the immune evasion process remains unclarified. Previous study found that the tissue-dwelling helminth Trichinella spiralis produces calreticulin (TsCRT) which binds C1q to inhibit activation of the complement classical pathway. Here, we used X-ray crystallography to resolve the structure of truncated TsCRT (TsCRT Δ ), the first structure of helminth-derived CRT. TsCRT Δ was observed to share the same binding region on C1q with IgG based on the structure and molecular docking, which explains the inhibitory effect of TsCRT on C1q-IgG-initiated classical complement activation. Based on the key residues in TsCRT Δ involved in the binding activity to C1q, a 24 amino acid-peptide called P TsCRT was constructed that displayed strong C1q-binding activity and inhibited C1q-IgG-initiated classical complement activation. This study is the first to elucidate the structural basis of the role of TsCRT in immune evasion, providing an approach to develop helminth-derived bifunctional peptides as vaccine target to prevent parasite infections or as a therapeutic agent to treat complementrelated autoimmune diseases.